2021
DOI: 10.1162/tacl_a_00435
|View full text |Cite
|
Sign up to set email alerts
|

Weisfeiler-Leman in the Bamboo: Novel AMR Graph Metrics and a Benchmark for AMR Graph Similarity

Abstract: Several metrics have been proposed for assessing the similarity of (abstract) meaning representations (AMRs), but little is known about how they relate to human similarity ratings. Moreover, the current metrics have complementary strengths and weaknesses: Some emphasize speed, while others make the alignment of graph structures explicit, at the price of a costly alignment step. In this work we propose new Weisfeiler-Leman AMR similarity metrics that unify the strengths of previous metrics, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Original datasets contain a set of pairs of sentences with a human-labeled similarity score. Opitz et al (2021) utilized a strong parser to construct AMR graph pairs from sentence pairs and normalized similarity scores to the range [0, 1] to facilitate standardized evaluation. There are 1379 and 4927 test instances in the two datasets, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Original datasets contain a set of pairs of sentences with a human-labeled similarity score. Opitz et al (2021) utilized a strong parser to construct AMR graph pairs from sentence pairs and normalized similarity scores to the range [0, 1] to facilitate standardized evaluation. There are 1379 and 4927 test instances in the two datasets, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The alignment process, which has been proved as NP-hard, limits the efficiency of SMATCH, especially as the sizes of AMR graphs increase. Another weakness is that the structural matching is insufficient for meaning similarity assessment and fragile in concept synonym replacement and structure deformation (Blloshmi et al, 2020;Opitz et al, 2021).…”
Section: Existing Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we explore Abstract Meaning Representation (AMR) (Banarescu et al, 2013), a semantic formalism that has received much research interest (Song et al, 2018;Guo et al, 2019;Ribeiro et al, , 2021aOpitz et al, 2020Opitz et al, , 2021Fu et al, 2021) and has been shown to benefit downstream tasks such as spoken language understanding (Damonte et al, 2019), machine translation (Song et al, 2019), commonsense reasoning (Lim et al, 2020), and question answering (Kapanipathi et al, 2021;Bornea et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we explore Abstract Meaning Representation (AMR) (Banarescu et al, 2013), a semantic formalism that has received much research interest (Song et al, 2018;Guo et al, 2019;Ribeiro et al, , 2021aOpitz et al, 2020Opitz et al, , 2021Fu et al, 2021) and has been shown to benefit downstream tasks such as spoken language understanding (Damonte et al, 2019), machine translation (Song et al, 2019), commonsense reasoning (Lim et al, 2020), and question answering (Kapanipathi et al, 2021;Bornea et al, 2021).…”
Section: Introductionmentioning
confidence: 99%